2020
DOI: 10.1093/brain/awaa139
|View full text |Cite
|
Sign up to set email alerts
|

Excess Lipin enzyme activity contributes to TOR1A recessive disease and DYT-TOR1A dystonia

Abstract: TOR1A/TorsinA mutations cause two incurable diseases: a recessive congenital syndrome that can be lethal, and a dominantly-inherited childhood-onset dystonia (DYT-TOR1A). TorsinA has been linked to phosphatidic acid lipid metabolism in Drosophila melanogaster. Here we evaluate the role of phosphatidic acid phosphatase (PAP) enzymes in TOR1A diseases using induced pluripotent stem cell-derived neurons from patients, and mouse models of recessive Tor1a disease. We find that Lipin PAP enzyme activity is abnormall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Lipidomics has successfully been applied to study disease and disease-related mechanisms in many different indications. Among these are neurological disorders [Bosch-Queralt et al, 2021, Cascalho et al, 2020, liver disease [Parker et al, 2019] and cancer [Bi et al, 2019, Peck et al, 2016, Saliakoura et al, 2020, resulting in the identification of potential drug targets involved in lipid metabolism [Matsushita et al, 2021]. A primary model for these studies is the mouse Mus musculus.…”
Section: Introductionmentioning
confidence: 99%
“…Lipidomics has successfully been applied to study disease and disease-related mechanisms in many different indications. Among these are neurological disorders [Bosch-Queralt et al, 2021, Cascalho et al, 2020, liver disease [Parker et al, 2019] and cancer [Bi et al, 2019, Peck et al, 2016, Saliakoura et al, 2020, resulting in the identification of potential drug targets involved in lipid metabolism [Matsushita et al, 2021]. A primary model for these studies is the mouse Mus musculus.…”
Section: Introductionmentioning
confidence: 99%
“…Changes not amenable to torsinA repletion likely include ChI degeneration, as initiating torsinA replacement after ChI loss is ineffective. An association between prevention of ChI degeneration and behavioral rescue has been demonstrated in torsinA LOF models (44,45), further supporting this connection. Striatal dysfunction secondary to ChI loss and dysfunction likely causes additional abnormalities of connectivity and function within and beyond the striatum, and failure to restore torsinA in these other neural elements may in part account for the incomplete motor rescue we observe.…”
Section: Discussionmentioning
confidence: 56%
“…59 Our results extend these observations further to human disease-specific variation and suggest that a complex interplay of dysregulated lysosomal sphingolipid metabolism, disrupted oligodendrocyte differentiation, and altered myelin formation and/or maintenance may contribute to the molecular and cellular mechanisms underlying THAP1 disease. [81][82][83][84] Although overt demyelination has not been specifically documented in dystonia, neuroimaging studies have reported white matter abnormalities in multiple forms of the disease, including: (1) syndromes associated with genetic variation in TOR1A, THAP1, SGCE, TAF1, KMT2B, and COL6A3 20,69,[85][86][87][88][89] ; and (2) idiopathic cases of cervical dystonia, writer's cramp, laryngeal dystonia, and blepharospasm. [90][91][92][93] The mechanisms underlying these disturbances in white matter tracts are not known, and further investigation is needed to determine if they reflect common defects in any of the pathways perturbed by genetic variation in THAP1.…”
Section: Discussionmentioning
confidence: 99%